2006
DOI: 10.1002/gps.1624
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and general health problems following myocardial infarction (Post‐MI PTSD) among older patients: the role of personality

Abstract: MI older patients could manifest PTSD symptoms and general health problems following their MI. Personality traits, particularly neuroticism and antagonism, played a role in the manifestation of these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 91 publications
(101 reference statements)
6
37
1
3
Order By: Relevance
“…The findings indicate that a high score within the domain of neuroticism can comprise a predisposing risk factor to the development of symptoms of PTSD, and a high score within the domain of agreeableness can comprise a predisposing resilience factor. These findings are consistent with previous work (e.g., Chung, Berger, Jones & Rudd, 2006;Fauerbach et al, 2000;Hyer et al, 1994;Ribi et al, 2007;Rubin, Berntsen, & Bohni, 2008;Talbert et al, 1993). However the statistical analysis also revealed that preexisting personality traits cannot by themselves explain the development of symptoms of PTSD among veterans, since a number of cofounders were identified.…”
Section: Discussionsupporting
confidence: 91%
“…The findings indicate that a high score within the domain of neuroticism can comprise a predisposing risk factor to the development of symptoms of PTSD, and a high score within the domain of agreeableness can comprise a predisposing resilience factor. These findings are consistent with previous work (e.g., Chung, Berger, Jones & Rudd, 2006;Fauerbach et al, 2000;Hyer et al, 1994;Ribi et al, 2007;Rubin, Berntsen, & Bohni, 2008;Talbert et al, 1993). However the statistical analysis also revealed that preexisting personality traits cannot by themselves explain the development of symptoms of PTSD among veterans, since a number of cofounders were identified.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that neuroticism has a positive relation with generalized anxiety disorder (Bienvenu et al, 2001), whilst extraversion is negatively associated to these disorders (Gomez and Francis, 2003). Openness to experience and conscientiousness associate negatively to obsessive compulsive disorder and agreeableness associates to posttraumatic disorder (Chung, Berger, Jones, and Rudd, 2006 As for depressive symptoms, neuroticism has been considered to influence the onset of depressive disorder (Goodwin and Gotlib, 2004;Peñate, Perestelo, Bethencourt, and Ramírez, 2009). It has also been shown that when somebody is suffering from a depressive disorder scores for neuroticism and extraversion are influenced by the depressive state, these scores will again change once the depressive symptoms recede, whilst the other three traits remain stable (Griens et al, 2002).…”
Section: Personality and Psychological Healthmentioning
confidence: 99%
“…For example, heighten levels of death anxiety have been observed following traumas such as exposure to toxic material [1], technological disasters [2][3][4], war situations [5] as well as a range of other traumas [6][7][8][9]. Furthermore, studies have documented high levels of comorbidity between death anxiety and other symptoms of psychopathology frequently observed following trauma exposure, such as anxiety and depression [2,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%